Kontestasi Antar Kelompok Muslim di Bima (Studi Perebutan Wacana Atas Perkembangan Pandangan Keislaman di Ruang Publik - Mustakira (CV. Creative Tugu Pena, 2024)
Contestation between Muslim groups in Bima contested the discourse on the development of Islamic views in the public sphere. This type of research is qualitative with the approaches used are: phenomenological and sociology approaches of religion. The sources of data for this research are leaders of Islamic organizations, regional leaders, community leaders, and youth leaders. Furthermore, the data collection methods used are observation, interviews, documentation and reference searches. Then the data processing and data analysis techniques are carried out through three stages, namely: data reduction, data presentation, and conclusion drawn. The results of this study show that the actors of the Islamic group of the Bima community each carry out their mission by contesting in influencing the socio-religious dynamics of the community, the movement for public discourse is carried out by their respective cadres in the form of conveying understanding based on their perspective on the Qur'an text which is the socio-cultural background of its founder, the impact of other actors makes the resistance of the Islamic group of the community and compartmentalized. Keywords: Contestation, Islamic Groups in Bima, Bima Community